PET/CT-Based Characterization of 18F-FDG Uptake in Various Tissues Reveals Novel Potential Contributions to Coronary Artery Disease in Psoriatic Arthritis - Schwartz, Daniella M.; Parel, Philip; Li, Haiou; Sorokin, Alexander V.; Berg, Alexander R.; Chen, Marcus; Dey, Amit; Hong, Christin G.; Playford, Martin; Sylvester, McKella; Teague, Heather; Siegel, Evan; et al. (Frontiers in Immunology, 2022)
Background and Objectives Psoriasis is a heterogeneous inflammatory disease that involves the skin, joints, liver, heart, and other organs. Psoriatic arthritis (PsA) is associated with cardiovascular disease (CVD), but the relative contributions of inflammatory and metabolic dysregulation to CVD are incompletely understood. We set out to discover novel potential contributors to CVD in PsA patients by comprehensively phenotyping a cohort of PsA patients using these advanced technologies. Methods In this cross-sectional analysis of a cohort study, we investigated associations of systemic inflammation and metabolic dysregulation with Coronary CT angiography (CCTA)-proven coronary artery disease (CAD) in 39 subjects with PsA. We measured traditional CVD risk factors (blood pressure, BMI, diabetes, age, sex, smoking), serum markers of systemic inflammation (hsCRP, GlycA) and metabolic dysfunction (cholesterol efflux capacity), and inflammatory cytokines (IL-1, IL-6, IL-12/IL-23, IL-17A, TNF-, IFN-). We also incorporated radiographic measures of metabolic dysfunction (visceral and subcutaneous adipose volume) and tissue-specific inflammation (positron emission tomography-computed tomography, PET-CT). To quantify relative contributions of FDG (fluorodeoxyglucose) uptake and adiposity to coronary plaque, we performed multiple linear regression, controlling for Framingham risk score (FRS) and FRS + visceral adiposity. Results Compared with non-psoriatic volunteers, subjects with PsA had elevated markers of metabolic and inflammatory disease, which was more pronounced in subjects with moderate-to-severe skin disease. This included visceral (p = 0.005) and subcutaneous (p = 0.004) adiposity, body mass index (p = 0.001), hemoglobin A1C (p = 0.037), high sensitivity C-reactive protein (p = 0.005), IL-6 (p = 0.003), IFN-g (p = 0.006), and liver FDG uptake (p = 0.03). In subjects with PsA, visceral adiposity correlated significantly with subclinical CAD (standardized beta = 0.681, p = 0.002), as did FDG uptake in bone marrow (standardized beta = 0.488, p = 0.008), liver (standardized beta = 0.619, p < 0.001), spleen (standardized beta = 0.523, p = 0.004), and subcutaneous adipose (standardized beta = 0.524, p = 0.003). Interpretation Together, these findings reveal inflammatory and metabolic potential contributors to subclinical CAD in PsA, including adipose inflammation, and suggesting novel targets for CVD prevention and treatment in PsA.